2013
DOI: 10.1136/bmjopen-2013-002672
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular specific activity of ibuprofen and the other 2-arylpropanoic acids using the HT-SPOTi whole-cell phenotypic assay

Abstract: ObjectivesLead antituberculosis (anti-TB) molecules with novel mechanisms of action are urgently required to fuel the anti-TB drug discovery pipeline. The aim of this study was to validate the use of the high-throughput spot culture growth inhibition (HT-SPOTi) assay for screening libraries of compounds against Mycobacterium tuberculosis and to study the inhibitory effect of ibuprofen (IBP) and the other 2-arylpropanoic acids on the growth inhibition of M tuberculosis and other mycobacterial species.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 48 publications
1
80
0
1
Order By: Relevance
“…was performed using the spot culture growth inhibition assay (SPOTi) in 24 well plates. 26 A seed 104 culture of each bacteria was prepared in Luria Bertani (LB) broth and grown overnight at 37 ºC with 105 shaking at 200 rpm. Rhodococcus sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…was performed using the spot culture growth inhibition assay (SPOTi) in 24 well plates. 26 A seed 104 culture of each bacteria was prepared in Luria Bertani (LB) broth and grown overnight at 37 ºC with 105 shaking at 200 rpm. Rhodococcus sp.…”
mentioning
confidence: 99%
“…The 118 antimycobacterial activities of the compounds were tested following the HT-SPOTi guidelines. 26,27 HT-119…”
mentioning
confidence: 99%
“…SPOTi is a solid-culture based technique wherein an optimised number of bacteria are spotted on to agar containing a series of dilutions of inhibitor molecules. [131][132][133] This method has been adapted to 96-well microplate format thereby increasing the throughput.…”
Section: The Search For Novel Therapeutic Targetsmentioning
confidence: 99%
“…[145][146][147] Dr Bhakta and his research group reported the common, over-the-counter non-steroidal anti-inflammatory drugs (NSAIDs), ibuprofen and carprofen to be antitubercular specific. 131,148,149 They were found to be active against drug resistant strains and stationary phase mycobacteria. The endogenous mechanism of action of these drugs is still under debate, however, transcriptomic analyses reveal that the drugs may have pleiotropic effects on the pathogen.…”
Section: The Promising Molecules and Natural Productsmentioning
confidence: 99%
“…However this method depends on the availability of resistant mutants and this can be limited in some cases (Gold et al, 2012a;Guzman et al, 2013). The application of whole genome transcriptomics is another alternative way to examine the mechanism of action of new molecules.…”
Section: In Vitro Studiesmentioning
confidence: 99%